The transfer effects of computational thinking: A systematic review with meta‐analysis and qualitative synthesis. - Ye, Jiachu; Lai, Xiaoyan; Wong, Gary Ka‐Wai (Journal of Computer Assisted Learning, 2022)
Background: Computational thinking (CT) is regarded as an essential 21st‐century skill, and attempts have been made to integrate it into other subjects. Instructional approaches to CT development and assessment in the field of computer science have attracted global attention, but the influence of CT skills on other subject areas is under‐researched. Objective: Our goal is to investigate the transfer effects of CT in different subject areas and examine the educational characteristics of CT intervention approaches that promote the transfer of learning. Method: We carefully selected and reviewed 55 empirical studies from leading bibliographic databases and examined the transfer of CT using a meta‐analysis and a qualitative synthesis. Results and Conclusions: We identified and summarized these effects in the fields of mathematics, science, engineering and the humanities. A meta‐analysis of these studies identified a generally significant effect of the transfer of CT skills to other subject areas. We also explored the characteristics of CT interventions that aid the transfer of learning by qualitatively assessing the identified studies. The results of the review offer a holistic view of the trends in CT transfer research that can be used as a reference for both researchers and instructors. Lay Description: What is already known about this topic: Computational thinking (CT) has been developed into cross‐disciplinary literacy and can lead to innovations in various academic fields.There is a need for a systematic understanding of the transfer effects of CT to improve the influence of CT and promote CT integration across domains. What this paper adds: Our review identified several subject areas beyond computer science in which the transfer effects of CT were observed.Our analysis revealed that the transfer of CT has a significant positive effect on students' learning in areas beyond computer science.Our review synthesized a series of intervention guidelines that can promote the transfer of learning in CT education. Implications for practitioners: Research on the transfer of CT in engineering and non‐STEM domains is required for a more comprehensive understanding of CT skills.Instructional design in CT education should attend to the facilitation of the transfer of learning to maximize the benefits of CT acquisition.